Thermal expansion of (FeIn2S4)0.5×(AgIn5S8)0.5 single crystals - T. H. Barugu (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
(FeIn2S4)0.5×(AgIn5S8)0.5 single crystals have been grown with method of directional crystallization. Their composition and structure were determined. It is seen that the pointed compounds and solid solutions are crystallized in the spinal cubic structure. The elementary cell parameters was calculated with the least square method. The thermal expansion was measured by a dilatometric method, the coefficient of thermal expansion was determined. Debye temperature and the mean square dynamic displacements of atoms for grown single crystals were calculated.